RELEVANCE ANALYSIS OF CIVIL ENGINEERING COMPETENCY ACCORDING TO THE CONSTRUCTION INDUSTRY NEEDS IN VOCATIONAL HIGH SCHOOL - Rihab Wit Daryono; Muhammad Bachrawi Luthfi; Yayan Adrianova Eka Tuah (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2022)
Vocational High School (VHS) graduates as new workers are expected to be able to enter the workforce immediately after completing their education with the skills they have. But in reality, many graduates from vocational students do not work according to their field of expertise. This study aims to reveal competencies according to standards and needed by the construction industry and how much relevance is the level of competence in the curriculum and implemented in schools. The study was conducted in 15 construction industries with the characteristics of the respondents, namely directors, project and site managers, estimators, senior engineers and drafters, and architects. This type of research is quantitative descriptive research. The instrument, which consisted of 37 competency items, was validated using Exploratory Factor Analysis (EFA) techniques and the reliability was based on the Average Variance Extracted and Construct Reliability (CR) values. Overall, the competency instrument has met the Goodness of Fit (GoF) of construct validity and reliability. The results of the study reveal the level of relevance of civil engineering competencies based on three aspects, namely basic knowledge, work skills, and personal, obtaining results of 80.856% with relevant categories. These results are a reflection of the percentage of the construction service industry's needs for the competencies mastered by civil engineering graduates. This can be interpreted that the curriculum used in schools has taken into account the needs of the industry.